Curcumin Inhibits the Proteinase-Activated Receptor-2-Triggered Prostaglandin E2 Production by Suppressing Cyclooxygenase-2 Upregulation and Akt-Dependent Activation of Nuclear Factor-κB in Human Lung Epithelial Cells - Kazumi Moriyuki; Fumiko Sekiguchi; Kaori Matsubara; Hiroyuki Nishikawa; Atsufumi Kawabata (Elsevier, 2010)
We performed this study to determine if curcumin affects pro-inflammatory responses to activation of proteinase-activated receptor-2 (PAR2) in human pulmonary adenocarcinoma A549 cells. Curcumin completely inhibited the PAR2-triggered prostaglandin E2 (PGE2) production, but notably not interleukin-8 release. Cyclooxygenase-2 (COX-2) upregulation, but not its upstream activation of mitogen-activated protein kinases, caused by PAR2 stimulation was partially inhibited by curcumin. Curcumin inhibited the PAR2-triggered phosphorylation of I-κB, an indicator for nuclear factor-κB (NF-κB) activation, and also its upstream signal Akt, which is known to contribute to PAR2-triggered PGE2 formation, but not COX-2 upregulation. Collectively, curcumin inhibits the PAR2-triggered PGE2 production by suppressing COX-2 upregulation and Akt/NF-κB signals in A549 cells. Keywords:: curcumin, proteinase-activated receptor-2, prostaglandin E2